Implementation of Scientific Approach In Islamic Education Learning - Huda, Mualimul (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study explains how to implement a scientific approach in learning Islamic Religious Education (PAI) subjects. This research also explores several problems implementing a scientific approach to the issue of Islamic Religious Education. This research uses a descriptive qualitative method. They are collecting data using interview documentation and observation. Researchers conducted semi-structured interviews to obtain comprehensive data—informants in research, among them school principals, PAI teachers, and students. Data validity and validity tests were conducted using source, technique, and time triangulation methods. Data analysis was carried out with data reduction, data presentation, and verification stages. The results of the study show that a scientific approach to Islamic subjects is carried out in the four fields of study, namely the study of the Al-Qur'an-Hadith, Akidah- Akhlak, Fiqh, and History of Islamic Culture. Learning activities are done by observing, asking, exploring, associating, and communicating. The scientific approach in PAI subjects can be applied with a material approach and a methodical approach. Islamic education material in the study of moral education, jurisprudence, and Islamic cultural history can be used with a material approach. In comparison, material for faith and faith can be applied methodically. The material approach provides a broader explanation related to social practices and contexts in everyday life. The method approach is carried out by directing students to explore the resources of teaching materials available in the library. There are several supporting and inhibiting factors in implementing the scientific approach, among them necessity Skills teachers to integrate PAI material and scientific knowledge, student readiness, learning media, and infrastructure.